Effect of frost damage on leaf macronutrient status of eight apple cultivars in integrated apple orchard in Eastern-Hungary - Nagy, P. T.; Kátai, J.; Nyéki, J.; Szabó, Z. (International Journal of Horticultural Science, 2008)
The year of 2007 was critical for fruit growers in the region of Easter-Hungary. Several orchards were suffered frost damages. Significant frost damage was also happened in the orchard of Tedej Rt., which caused total fruit failure in the orchard. Our study was conducted in the integrated apple orchard (Malus domestics Borkh.) established on a lowland chemozem soil in East-Hungary, to investigate how frost changes the mineral content of different apple species. Leaf samples were collected 100 days after full bloom both in 2006 and 2007. The concentrations of nitrogen, phosphorous, potassium, calcium and magnesium were measured in leaves. The absence of fruits caused a smaller accumulation of nitrogen and magnesium in leaves. Falling down of flowers and fruit sets hindered the translocation of the uptaken phosphorous, potassium and calcium towards fruit sets. Due to fruit failure the vegetative processes became dominant. Leaves larger amount of phosphorous, potassium and calcium stored. Besides the absolute element content, the ratio of the different elements was also determined. Majority of calculated ratios were removed from optimal values due to frost. Both absolute content of nutrients and their ratios pointed out that the frost damage significantly affected the uptake of nutrients and their storing processes.